Are Carbon Leader Indexes Related with Carbon Prices under Different Regimes? - Koy, Ayben; Okay, Güçlü (International Journal of Energy Economics and Policy, 2020)
With the rising importance of carbon markets, the new derived financial instruments and indicator indexes related to carbon markets have been raising researchers’ appetite. According to that aspect, to investigate the relationship between price formation in carbon markets and equity prices of these firms trading in carbon markets is one of the aims of this study. This study examines CO2 prices of European Union Emission Allowances and daily closing values of MSCI Low Carbon Leaders USD Dollar Price Indexes via Markov Regime Switching Models from a non-linear perspective. Among the findings, there is a relationship between the index derived from the stock performances of North American firms trading in carbon markets and carbon prices. Furthermore, the strength of the relationship increases during periods of recession identified by the MRS models. Keywords: Carbon markets, energy prices, Markov Regime Switching Model, Kyoto Protocol. JEL Classifications: F30, G15 DOI: https://doi.org/10.32479/ijeep.9193